Self-Sustenance through Studentpreneurship among Students of Nnamdi Azikiwe University, Awka - Taiwo Abdulahi (Saniya Institute, 2025)
This study, titled Self-Sustenance Through Studentpreneurship Among Students of Nnamdi Azikiwe University, Awka, investigates how entrepreneurial activities contribute to financial independence and sustainable livelihoods among students. The research examined three objectives: the effect of selling products in the classroom on competitive edge, the influence of meeting students’ needs on self-employment, and the role of product customisation in meeting financial obligations. A descriptive survey research design was adopted to target studentpreneurs within the university community. From a population of 53,707 students, a sample of 398 was selected using Taro Yamane’s formula, with 85 active studentpreneurs purposively selected for detailed analysis. Data were collected using a validated and reliable questionnaire (Cronbach’s Alpha: 0.78–0.83) and analysed with descriptive and inferential statistics, including Pearson correlation and regression. Findings revealed that selling products in the classroom significantly enhanced competitive edge, explaining 68.9% of its variance (R² = .689, F = 183.557, p = .000). Meeting students’ needs strongly contributed to self-employment, accounting for 93.3% of variance (R² = .933, F = 76.640, p = .000), with capital and demand alignment as key predictors. Furthermore, customising products and services significantly improved students’ ability to meet financial obligations, accounting for 92% of the variance (R² = .920, F = 310.236, p = .000). The study concludes that student entrepreneurship fosters self-sufficiency through creativity, demand-driven ventures, and product customisation. It recommends that universities support responsible classroom sales, encourage market-driven innovation, and establish incubation hubs to enhance entrepreneurial training and product development.